MULTIPHYSIC MODEL DEVELOPMENT OF A HYBRID VEHICLE WITH TWO-WHEEL DRIVE (Global Journal of Advanced Engineering Technologies and Sciences, 2016)
Vehicles are a fundamental part of our daily lives. However, conventional cars are the main source of pollution in the 21st century. For that reason, industries have to concentrate more on alternative energy and transport’s means in order to avoid energy crisis. Environmental worries motivate the world’s automobile industries to change conventional vehicles into low-emission and zero-emission vehicles. So far, the most promising technologies are hybrid vehicles that contain two or many power sources and which we find several architectures. In this paper, we developed a dynamic model of hybrid vehicle with two-wheel drive and its control unit using AMESim environment. The simulation results of this multidisciplinary system were used for an operating cycle NEDC (New European Driving Cycle) to optimize fuel and battery consumptions.)